PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS NASABAH PADA PT. BPR PANCUR BANUA KHATULISTIWA SUNGAI PINYUH - B11106120, Albert Tulus. BN (Jurnal Manajemen Update, 2013)
Banking industry have hand in glove related/relevant to its consumer, because relation between client and banking represent one unity. Both of the components is requiring each other. On that account, bank have toearn to give best service to all its client so that good relation among both parties. In this research, variable satisfaction and trust used to measure customer loyality. Object in this research is PT BPR Pancur Banua Khatulistiwa client. Quantitative Analysis in this research is done multiple linear regression analyse. While analysis is qualitative obtained from intepretation respondent in this research. Result of research indicate that variable satisfaction and trust have simultaneously influence to cutomer loyalty. Partially only trust variable affecting to loyalty with a significance value 0,000 while satisfaction 0,110 means not affect to loyalty. Key words : trust, satisfaction, and cutomer loyalty